Symptom management in a patient with advanced prostate cancer - Blacharska-Krzanowska, Katarzyna; Strzępek, Katarzyna; Cieślikowski, Damian; Kozlowski, Michael (Medycyna Paliatywna/Palliative Medicine, 2018)
Pain is one of the most frequently occurring symptoms among patients suffering from advanced cancer. Its management often presents a challenge for a physician, requiring complex strategies to provide adequate relief. Breakthrough pain, in particular, with its severe intensity and often unpredictable onset, can be distressing not only for patients and caregivers but also for clinicians. Currently breakthrough pain can be effectively treated with immediate release opioids, as well as intranasal and sublingual fentanyl preparations. In this article, we present the case of a patient with advanced prostate cancer suffering from pain symptoms due to several different pathomechanisms. While complex pharmacologic strategies were required, adequate pain control was ultimately achieved.